Does the Stock Market Rationally Reflect Fundamental Values? - SUMMERS, LAWRENCE H. (Journal of Finance, 1986)
ABSTRACT This paper examines the power of statistical tests commonly used to evaluate the efficiency of speculative markets. It shows that these tests have very low power. Market valuations can differ substantially and persistently from the rational expectation of the present value of cash flows without leaving statistically discernible traces in the pattern of ex‐post returns. This observation implies that speculation is unlikely to ensure rational valuations, since similar problems of identification plague both financial economists and would be speculators.